Os desafios relacionados ao planejamento de parcerias público-privadas no Brasil e o papel do procedimento de manifestação de interesse como instrumento de acréscimo de eficiência aos projetos: um olhar sobre a experiência em Minas Gerais - Antunes, Mariana de Araújo (2018)
This study addresses the challenge of overcoming obstacles to the consolidation of the PublicPrivate Partnerships model as an alternative to efficient public enterprises, as well as the role of the Expression of Interest Procedure to remedy them. In view of the challenges that still lie in the realization of PPPs in Brazil, the work promotes a reflection about the convergence between the good practices pointed out by the theory developed on the subject in recent years and the reality of the practice of the provision of public activities through of PPPs in the country. Considering that the institutions and the competences accumulated in the public sector are central elements for the development of Public-Private Partnerships, the work takes as analytical reference the State of Minas Gerais, realizing an exploratory illustration of the experience of Minas Gerais with projects of PPP and with the of PMIs. The proposed analysis was based on bibliographical research, documentary review and unstructured interviews with public servants who work with the feasibility of PPP projects. The documentary review was based mainly on the information and documents made available by Prodemge on the Expression of Interest of the Minas Gerais Technology Platform project carried out in 2017, which is an object of study. The analysis of the conduction of said PMI allowed to verify that the last experience of Minas Gerais in the edition and conduction of a procedure of this nature was highly promising. In general, it can be said that the conduction of the PMI of the Technological Platform was in accordance with the best practices pointed out in the theory for the Conduct of Procedures of Manifestation of Interest. This study points to the conclusion that the good practices identified in conducting the PMI studied may be a reflection of the conjunction of experiences of experienced public contractors and of the BDMG, positively influencing the conduct of said procedure and generating gains of organizational knowledge. In this sense, the result of the research reinforces the conclusion about the key role of the institutions for the development of resources and procedures aimed at the development of Public Private Partnerships in Brazil.